Status gizi sebagai faktor prognosis penderita karsinoma endometrium - Heru Pradjatmo; Deyna Primavita Pahlevi (Jurnal Gizi Klinik Indonesia, 2013)
Background: In Indonesia, endometrial cancer is the third gynaecologic cancer after cervical and ovarian cancers. Various factors affect the survival of the patients, however, which factors affect the survival of endometrial carcinoma patients in Dr. Sardjito Hospital remain unclear. A research is therefore needed in order to determine the survival and the prognostic factors.Objective: To investigate the prognostic factors that affect the survival of endometrial carcinoma patients who had been admitted to Dr. Sardjito Hospital.Method: The study design was retrospective cohort. The subjects were patients with endometrial carcinoma who were treated in Dr. Sardjito Hospital from 1st of January 2006 until 31st of December 2011. Kaplan-Meier analysis was performed to analyze several factors that influenced the survival of the patients. The differences of survival were analyzed with log rank test while the prognostic factors influencing the survival were analyzed using Cox regression.Results: 68 endometrial carcinoma patients were recruited as the subjects for the study. The median survival of endometrial carcinoma patients 52 months for those on early stage and 17 months on advanced stage (p≤0.01). The prognostic factors affecting survival that has been found statistically and clinically significant was the stage of the disease (p=0.002; HR=6.175; 95% CI=1.1980 to 19.25). Meanwhile, the nutritional status of patients with low, normal, and high BMIs score showed increased survival rate as indicated by the HR values of 1; 0.768; and 0.311 respectively.Conclusion: The prognostic factor that was clinically and statistically significant influenced the survival was the stage of the disease, while the nutritional status of patients was found clinically significant as the prognostic survival of the patients.